2022
DOI: 10.36065/robrac.v31i90.1557
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças no atendimento odontopediátrico e uso de procedimentos de mínima intervenção durante a pandemia de COVID-19

Abstract: Para minimizar o risco de contaminação pelo COVID-19 foram propostas mudanças no atendimento odontológico e medidas adicionais de biossegurança. Pouco se sabe sobre a adesão dos odontopediatrias a essas orientações. Os objetivos deste estudo transversal foram verificar o impacto da pandemia de COVID-19 no atendimento odontopediátrico e se os odontopediatras adotaram procedimentos minimamente invasivos (PMI) para manejo da cárie dentária durante este período. Um formulário eletrônico foi enviado aos odontopedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Considering our results, despite some significant differences found between the dentists' attitudes performed before and during the COVID-19 pandemic, it was possible to verify that the magnitude of the effect was usually low, which demonstrated that there was no impact of COVID-19 on the use of MI techniques by Brazilian dentists. The results found in the present study corroborate with those of Braga et al [2022]. These authors also evaluated and compared the use of MI techniques by dentists before and during COVID-19 pandemic but only with pediatric dentists from a unique Brazilian state.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering our results, despite some significant differences found between the dentists' attitudes performed before and during the COVID-19 pandemic, it was possible to verify that the magnitude of the effect was usually low, which demonstrated that there was no impact of COVID-19 on the use of MI techniques by Brazilian dentists. The results found in the present study corroborate with those of Braga et al [2022]. These authors also evaluated and compared the use of MI techniques by dentists before and during COVID-19 pandemic but only with pediatric dentists from a unique Brazilian state.…”
Section: Discussionsupporting
confidence: 88%
“…In relation to the resin infiltrants, it is considered an expensive procedure [American Academy of Paediatric Dentistry, 2016; Slayton et al, 2018], reason that can justify their low use in both periods evaluated in the present study. Braga et al [2022] also observed similar results with resin infiltrants.…”
Section: Discussionsupporting
confidence: 75%
“…For dental practice, a series of regulations systematically guided the postponement of elective care in oral health in all age groups, suggesting that only urgent and emergency procedures should be managed without restrictions. Such regulations considered the risk of transmission of SARS-CoV-2 between professionals and patients, especially through contact with saliva and the generation of aerosols (characteristic in some dental procedures) 17,18 . The postponement of consultations and procedures by pediatric dentists during the COVID-19 pandemic was a frequent and significant problem for children's oral health 19 .…”
Section: Discussionmentioning
confidence: 99%